Proučevanje manjšin in obmejnih območij v zgornjem Jadranu - raziskovalni pristopi in problemi v luči politične geografije - Bufon, Milan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
The author deals with the complexity of minority and border issues that make up the problem of studying contact areas in the upper Adriatic. The nexus of these issues is under the simultaneous influence of various factors contributing to the formation of different phenomenon typologies within the social dominance-minority relation, comprised of the situations of border national minority, territorial or regional minority and urban minority. Upper Adriatic has once again proven to be a most interesting "laboratory" for the introduction of new models in the consolidation of various institutional and everyday forms of inter-ethnic integration within the framework of the EU.
Keywords: politična geografija; obmejna območja; regije; prebivalstvo; narodne majnšine; obmejno sodelovanje; Slovenia; Slovenija; Italija; Italy; Croatia; Hrvaška